POWER RELATION DEPICTED IN JEANETTE WINTERSON’S ORANGES ARE NOT THE ONLY FRUIT - ASMORO, DHIAN ZHAFARINA CAHYO (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: power, discourse, Foucault, Jeanette Winterson, Oranges are not The Only Fruit Power spreads everywhere and it can influence people. Power is not always relatedwith government institution but also it comes from small unit like a family. Power holds by parents in a family can give a major impact to their children. Parents teach their children based on their values and norms they hold dear. That is why, sometimes the children is also influenced by their parents’ belief. Power also comes from society and religion institution. Society shapes the “normal” norm while religion institution which is considered as the highly oppressive institution, shapes which one is wrong and which one is right. In addition, this study observes how power relation is depicted in Oranges are not The Only Fruit especially in mother and daughter relationship in which the mother is attached to the religion power. Sociological approach is used in this study since it deals with human social relationships and institutions. It helps to discover how society at that time views one of the themes of this novel which is LGBT and how religion institution’s power reacts about it. This approach leads to the use of power relation theory to analyse how power can influence how someone view certain conditions and it can give such a major impacts to their life. The last, to discover how power relation is depicted in this novel, the concept of power and discourse purposed by Michele Foucault is used.The result of this research shows that power relations work inside from three sources.The first one is family, second one is society, and the last is religion institution which is the church. Power in this novel is also transferred by Jeanette’s mother to her daughter through discourse based on her view and belief. Jeanette’s mother’s attempt to prepare her daughter to become a missionary is failed since Jeanette resists her power about heterosexuality norm and she wants to stay true with her identity as a homosexual, no matter how strong the rejection comes from the church and society.The following researchers are suggested to analyze what is an orange represents from. Orange plays significant role in Jeanette’s life since her mother does not recognize any other fruits. Besides this suggestion, the following researchers can analyze on why religion plays important role in shaping society’s view.